2001
DOI: 10.1044/1092-4388(2001/093)
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Self-Reported Hearing Loss and Audiometry in a Cohort of New York Farmers

Abstract: The New York State Farm Family Health and Hazard Surveillance was conducted to assess the health status and safety practices among year-round adult farmers and farm residents in New York State and included a telephone interview survey of 1,727 persons from 552 farms. To determine the extent to which self-reported hearing loss is in agreement with audiometry, a subset of 376 participants who completed a hearing loss interview and pure-tone audiometry was analyzed. Thirty-six percent of the participants had self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 9 publications
6
75
3
2
Order By: Relevance
“…Self-perception of hearing loss seems to be in agreement with pure tone mean of medium frequencies (1, 2, 3 and 4 kHz) 16 and it is more frequent in subjects with moderately-severe hearing loss than among those with mild loss 8,23 . As to questions used, multiple-choice questions 14,24 presented lower sensitivity when compared to two-option questions.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Self-perception of hearing loss seems to be in agreement with pure tone mean of medium frequencies (1, 2, 3 and 4 kHz) 16 and it is more frequent in subjects with moderately-severe hearing loss than among those with mild loss 8,23 . As to questions used, multiple-choice questions 14,24 presented lower sensitivity when compared to two-option questions.…”
Section: Discussionsupporting
confidence: 48%
“…We selected 10 articles from MEDLINE and none from LILACS. We excluded one article because it did not provide isolated data on validity of the use of one single global question on hearing loss assessment compared to pure tone audiometry 16 , one article that did not specify the results in the elderly 17 , and another one that did not compare the results of one single question with audiometry 18 .…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…From a logistical and financial standpoint, it is challenging to obtain audiograms in such a large cohort. It has been shown in previous studies that compared with hearing loss diagnosed by audiogram, self-reported hearing loss is a relatively reliable indicator of hearing loss (22)(23)(24)(25). In addition, significant associations between other factors and risk of self-reported hearing loss have been observed using this method of assessment in NHS I and NHS II (14,(26)(27)(28)(29).…”
Section: Ascertainment Of Hearing Lossmentioning
confidence: 70%
“…The outcome of our study was self-reported hearing loss. Although pure-tone audiometry is considered the gold standard for diagnosing hearing loss, self-reported hearing loss has been shown to be a reliable indicator of hearing loss (22)(23)(24)(25). Furthermore, in a recent literature review, Chou et al (55) showed that a single question on perceived hearing loss was almost as accurate as a more detailed questionnaire or portable audiometric device for detecting hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Many people with NIHL fall into the former category. Gomez et al (2001) examined the relationship between audiometric thresholds and self-reported hearing difficulty for 376 farmers who were known to be exposed to potentially damaging levels of noise. The agreement between selfreport scores of hearing difficulty and audiometric thresholds was higher for the average across 1, 2, 3, and 4 kHz than for the average across 0.5, 1, and 2 kHz or across 3, 4, 6 and 8 kHz.…”
Section: Predicting Self-reported Hearing Difficulty Based On Audiomementioning
confidence: 99%